Strengthening the surveillance and information activities is urgent and essential to reduce the transmission force of SARS-CoV-2 - Teixeira, Maria Gloria (2021)
Universidade Federal da Bahia. Instituto de Saúde Coletiva. Salvador, BA, Brasil / Fundação Oswaldo Cruz. Centro de Integração de Dados e Conhecimentos para Saúde. Salvador, BA, Brasil.